Pharmcognostic, phytochemical and antibacterial studies on jasminum auriculatum - Sucharitha P A M; Madhu bindu M; U Salma S; R Mymuna S; Padmavathi P; Mansoor A K S.P; V Ramana P (International Journal of Pharmacy and Analytical Research, 2022)
Jasmine is a genus of shrubs and vines in the olive family Oleaceae with about 200 species throughout the world, out of which around 40 species are reported to be growing in India. Irrespective of the species, extracts from different parts such as leaves, stem, bark and roots of the Jasminum plants have been used in ethno -medicines for a long time. The aim of the present study is to screen the plant material for phytochemical constituents and antibacterial activity. An antimicrobial is a substance that kills or inhibits the growth of microorganisms such as bacteria, fungi or protozoans as well as destroying viruses. Antimicrobial drugs either kill microbes (microbicidal) or prevent the growth of microbes (microbiststic). Jasminum auriculatum is an evergreen shrub; native to Deccan Peninsula, Circars and Carnatic extending south wards to Travancore. The present study on pharmacognostical characteristic of Jasminum auriculatum provide useful information for its correct identity and help to differentiate from the closely related other species. Strains of bacteria Streptomyces aureus and Escherichia coli have been used for the study. The ethanolic extracts were used to find antibacterial activity by disc plate method and are showing very good reaction for carbohydrates, alkaloids, volatile oils, flavanoids, tannins, saponins, fats and oils and amino acids. This may be the reason for the very good antibacterial activity.